2021
DOI: 10.1186/s12964-021-00754-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis reveals cell communication triggered by macrophages associated with the reduction and exhaustion of CD8+ T cells in COVID-19

Abstract: Background The coronavirus disease 2019 (COVID-19) outbreak caused by severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) has become an ongoing pandemic. Understanding the respiratory immune microenvironment which is composed of multiple cell types, together with cell communication based on ligand–receptor interactions is important for developing vaccines, probing COVID-19 pathogenesis, and improving pandemic control measures. Methods A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…Our IPA analysis showed that activation of cytokines IL6, IL16, CXCL1, CXCL3, CXCL5, CXCL6, CXCL8, CXCL10, and CCL20 are a hallmark signature of cytokine response in COVID-19 patients [ 21 , 22 ]. Our finding is aligned with several reports from recent studies on SARS-CoV-2 induced transcriptomic landscape [ 23 25 ]. We also found increased levels of key pro-apoptotic factors like BCL2A1, LTF, SOX6, SPP1, and SYNE1.…”
Section: Discussionsupporting
confidence: 92%
“…Our IPA analysis showed that activation of cytokines IL6, IL16, CXCL1, CXCL3, CXCL5, CXCL6, CXCL8, CXCL10, and CCL20 are a hallmark signature of cytokine response in COVID-19 patients [ 21 , 22 ]. Our finding is aligned with several reports from recent studies on SARS-CoV-2 induced transcriptomic landscape [ 23 25 ]. We also found increased levels of key pro-apoptotic factors like BCL2A1, LTF, SOX6, SPP1, and SYNE1.…”
Section: Discussionsupporting
confidence: 92%
“…Other critical hub-high traffic genes in the blue module included EP300 ( 146 , 147 ), CDK1 ( 4 , 148 ), VEGFA ( 149 151 ), CTNNB1 ( 151 , 152 ), IL10 ( 9 , 153 155 ), SOCS1 , SOCS3 ( 156 ), SIRT1 ( 157 , 158 ), TFRC ( 159 161 ), HSP90AB1 ( 162 ), CYCS ( 163 ), EZR ( 164 ), TNFAIP3 , ICAM1 ( 10 ), and PIK3R1 ( 139 ) as well as TFs such as ATF4 ( 165 ), ATF3 ( 166 , 167 ), and BCL6 ( 152 ) which have important roles in pathogenesis of SARS-CoV-2, and some of which are potential therapeutic targets. For instance, SOCS1 / 3 antagonists may be prophylactic or therapeutic against the COVID-19 pandemic ( 156 ).…”
Section: Discussionmentioning
confidence: 99%
“…The repertoire of SARS-CoV-2-specific T cells in COVID-19 patients convalescent from mild disease covers a broad range of viral antigens including antigens from different VOCs. In contrast, in the majority of hospitalized patients reduced functionally active antiviral T cells are observed ( Bergamaschi et al, 2021 ; Bonifacius et al, 2021 ; He et al, 2021 ). Adoptive transfer of virus-specific T cells in different settings appears safe and effective ( Withers et al, 2017 ).…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, some patients do not mount an appropriate, efficient T cell reaction but exhibit inadequate immune responses ( Jarjour et al, 2021 ). Patients with severe COVID-19 generally develop lymphopenia, disruption of the T cell compartment, and CD8 + memory T cell exhaustion ( Bacher et al, 2020 ; He et al, 2021 ; Vigón et al, 2021 ). Reduced T cell counts and an increased granulocyte to lymphocyte ratio correlate with disease severity and are early predictive markers of an adverse course ( Kong et al, 2020 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%